Gastrin, gastric acid secretion, and gastric microflora in patients with rheumatoid arthritis. Issue 6 (June 1986) - Henriksson, K; Uvnäs-Moberg, K; Nord, C E; Johansson, C; Gullberg, R
Abstract : The relation between the basal and stimulated gastric acid secretion, plasma gastrin, and the gastric microflora was examined in 45 patients with rheumatoid arthritis. Sixteen patients (36%) had basal achlorhydria, and of these, 10 (22%) had achlorhydria or hypochlorhydria after stimulation with pentagastrin. The peak acid output and acidity showed inverse correlation with the disease duration but were not associated with age or with the degree of physical disability. Hypergastrinaemia was found in nine patients (20%), of whom 6 (13%) had significant titres of parietal cell antibody. The acidity of the peak acid output showed negative correlation with plasma gastrin. It was confirmed that the gastric secretory state is a determinant of plasma gastrin levels and in addition influences the growth of micro-organisms in the gastric lumen. The type of microflora in the non-acid stomach was similar to that found in the saliva. A subgroup of eight females was identified who showed low gastric acid secretion rates, positive bacterial cultures, and atlantoaxial subluxation. Gastrin- and insulin-like immunoreactivities were found in joint fluid. The concentrations reflected their plasma levels, suggesting that the peptides are not released at the inflammatory site, but rather that they reach synovial fluid from circulating blood.